Unveiling the Nexus between Good Corporate Governance, Human Capital, and Corporate Social Responsibility A Qualitative Study - Sri Utami Nurhasanah; Diani Austin; Nur Syifa Karimah (Jurnal Riset Akuntansi, 2023)
This qualitative study aims to explore the interconnectedness among good corporate governance (GCG), human capital, and corporate social responsibility (CSR) within organizations. The research employs a qualitative approach, utilizing in-depth interviews and thematic analysis to gather and interpret data. A purposive sampling technique is employed to select participants from diverse corporate backgrounds. The analysis reveals intricate relationships between GCG practices, human capital development, and CSR initiatives, highlighting the significant influence of effective governance structures on fostering a culture of responsibility towards stakeholders. Findings underscore the importance of nurturing human capital in promoting ethical business practices and sustainable CSR activities. This study contributes to the understanding of how GCG principles and investment in human capital intertwine to drive socially responsible behavior within corporations.